2017
DOI: 10.3389/fmicb.2017.00404
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of Non-photochemical Quenching as an Adaptive Strategy under Phosphorus Deprivation in the Dinoflagellate Karlodinium veneficum

Abstract: Intensified water column stratification due to global warming has the potential to decrease nutrient availability while increasing excess light for the photosynthesis of phytoplankton in the euphotic zone, which together will increase the need for photoprotective strategies such as non-photochemical quenching (NPQ). We investigated whether NPQ is enhanced and how it is regulated molecularly under phosphorus (P) deprivation in the dinoflagellate Karlodinium veneficum. We grew K. veneficum under P-replete and P-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
14
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 65 publications
2
14
0
Order By: Relevance
“…Decreasing g H + will increase transthylakoid proton motive force ( pmf ), thus lowering lumen pH and contributing to the activation of NPQ ( Kanazawa and Kramer, 2002 ). Earlier studies have indicated that NPQ is associated with the regulation of the photoprotective mechanism against high-light stress ( Lambrev et al, 2012 ; Cui et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…Decreasing g H + will increase transthylakoid proton motive force ( pmf ), thus lowering lumen pH and contributing to the activation of NPQ ( Kanazawa and Kramer, 2002 ). Earlier studies have indicated that NPQ is associated with the regulation of the photoprotective mechanism against high-light stress ( Lambrev et al, 2012 ; Cui et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…Given that the relative amount of carotenoid pigments in HS2 was increased under high salinity stress (Yun et al, 2019), enhancing the content of zeaxanthin by either upregulating VDE or downregulating ZEP may further enhance the halotolerance of HS2. Furthermore, although NPQ was not changed under high salinity stress, the elevation of NPQ has been denoted as one of the common algal responses under stress conditions (Cui, Zhang, & Lin, 2017). It would be, therefore, interesting to modulate the NPQ activity of HS2 as part of an effort to confer a greater halotolerance or induce a higher lipid productivity.…”
Section: Discussionmentioning
confidence: 99%
“…For example, it has been reported that high light intensity stress induces a decrease of F v /F m and an increase of NPQ of T. pseudonana (Zhang R. et al, 2017). In addition, Karlodinium veneficum cells respond to P deprivation by reconfiguring the metabolic landscape and up-tuning NPQ to increase the capacity to dissipate excess light energy and maintain the fluency of energy flow (Cui et al, 2017). In the present study, the values of NPQ in both AT and CK groups were low, while NPQ in the AT group was even lower than that of the CK group (Figure 2).…”
Section: Discussionmentioning
confidence: 99%